Libertarianism and social justice: Freedom as a political value - Solís Umaña, Mario (2026)
This article examines the tensions between the values of freedom and equality along the lines of an immanent critique to the libertarian approach— an approach that claims absolute priority to the value of freedom.  The article seeks to defend the idea of positive duties through a criticism of the negative absolute value of individual liberty.  The article also makes the case for positive duties in a more direct way, i.e., by showing how positive duties are consistent with the value of liberty as a political value.  The idea is to bring to light the thesis that positive duties are a necessary condition of liberty properly understood.